Effects of Shared Active Surface Technology on the Communication and Speech of Two Preschool Children With Disabilities. (March 2017) - Travers, Jason C.; Fefer, Sarah A.
Shared active surface (SAS) technology can be described as a supersized tablet computer for multiple simultaneous users. SAS technology has the potential to resolve issues historically associated with learning via single-user computer technology. This study reports findings of a SAS on the social communication and nonsocial speech of two preschool children with disabilities. An alternating treatments design was used to compare differences in these behaviors during a SAS technology–based coloring activity and analog coloring activity. Results indicated distinct differences in social communication and nonsocial speech across participants. Implications of the findings are discussed, and directions for potential research with this technology are provided.